Trouble in the West Egypt and the Persian Empire, 525-332 BC - Ruzicka, Stephen 1946- (Oxford studies in early empires, 2012)
This volume provides an account of the Persian-Egyptian War, a conflict that continued for nearly the 200-year duration of the Persian Empire